2012
DOI: 10.1093/jrr/rrs001
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of radiation-induced hematopoietic and gastrointestinal damage by Ex-RAD(R) in mice

Abstract: The aim of the present study was to assess recovery from hematopoietic and gastrointestinal damage by Ex-RAD ® , also known as ON01210.Na (4-carboxystyryl-4-chlorobenzylsulfone, sodium salt), after total body radiation. In our previous study, we reported that Ex-RAD, a small-molecule radioprotectant, enhances survival of mice exposed to gamma radiation, and prevents radiation-induced apoptosis as measured by the inhibition of radiation-induced protein 53 (p53) expression in cultured cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 33 publications
(52 reference statements)
3
46
0
Order By: Relevance
“…A significant increase in the number of apoptotic nuclei was observed at early time points only: 6 and 24 h and 2 weeks after irradiation, coinciding with the increased left ventricular expression of Bax. These results are in accordance with radiation-induced apoptosis in other organs, showing increased numbers of apoptotic cells from 6 h to several weeks after irradiation (3638). However, a recent study has demonstrated the presence of cleaved–caspase 3 at 13 months after local heart irradiation in the rat (14).…”
Section: Discussionsupporting
confidence: 88%
“…A significant increase in the number of apoptotic nuclei was observed at early time points only: 6 and 24 h and 2 weeks after irradiation, coinciding with the increased left ventricular expression of Bax. These results are in accordance with radiation-induced apoptosis in other organs, showing increased numbers of apoptotic cells from 6 h to several weeks after irradiation (3638). However, a recent study has demonstrated the presence of cleaved–caspase 3 at 13 months after local heart irradiation in the rat (14).…”
Section: Discussionsupporting
confidence: 88%
“…It is not possible to rank these radioprotectors as they are administered by different routes; however, if we were to compare the orally administered synthetic molecules, DMA could be ranked second: it has shown good radioprotection at a single dose, and no toxicity was observed up to 2000 mg/kg dose. Whereas a subcutaneous injection of 500 mg/kg bw of the radioprotective agent Ex-RAD (ON01210.Na; 4-carboxystyryl-4-chlorobenzylsulfone, sodium salt) in mice 24 hours and 15 minutes before radiation showed a DRF of 1.16 (Ghosh et al, 2012). A single subcutaneous injection of 200 mg/kg of genestein given at 24 hours before radiation showed a DRF of 1.16 (Landauer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The government has authorized the FDA to approve drugs based on adequate and well controlled animal studies, and the FDA has already approved four drugs based on five indications; however, Phase-I clinical safety testing for these drugs remains to be conducted. Currently, promising radiation countermeasure agents are in development, such as the new molecular entity CBLB 502 and the new chemical entity Ex-Rad, and AEOL-10150, which are being evaluated for clinical trials (Traynor et al 2006;Connolly and O'Neill 2012;Ghosh et al 2012). CCMAmi is a micelle encapsulated with amifostine, which is the first agent approved by the FDA as a radioprotector and chemoprotector (Spencer and Goa 1995).…”
Section: Discussionmentioning
confidence: 99%